2017
DOI: 10.1021/acsami.7b05519
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Encapsulation and Sustained Release of Basic Fibroblast Growth Factor in Nanofilm: Extension of the Feeding Cycle of Human Induced Pluripotent Stem Cell Culture

Abstract: Basic fibroblast growth factor (bFGF) has an established pivotal function in biomedical engineering, especially for the human pluripotent stem cells (iPSCs). However, the limitation of bFGF is the ease of denaturation under normal physiological conditions, inducing loss of its activity. In this study, we designed multi-trilayered nanofilm composed of a repeating polycation/polyanion/bFGF structure, which has high loading efficiency and short buildup time. We also investigated that the loading and release of bF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…This high abundance of bFGF levels in the CM of ARPE-19 cells is potentially useful as a stem cell maintenance medium, since sustained levels of bFGF improve the maintenance of human pluripotent and neural stem cells (Lotz et al, 2013). There have been persistent efforts to increase bFGF bioavailability (Han et al, 2017;Dvorak et al, 2018;Horighuchi et al, 2018;Titmarsh et al, 2017) in stem cell reserach because it has low thermal stability, being highly labile at 37°C (Levenstein et al, 2006;Furue et al, 2008), causing bFGF production efforts to suffer from batch-to-batch variations, and high costs of production (Ueki et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This high abundance of bFGF levels in the CM of ARPE-19 cells is potentially useful as a stem cell maintenance medium, since sustained levels of bFGF improve the maintenance of human pluripotent and neural stem cells (Lotz et al, 2013). There have been persistent efforts to increase bFGF bioavailability (Han et al, 2017;Dvorak et al, 2018;Horighuchi et al, 2018;Titmarsh et al, 2017) in stem cell reserach because it has low thermal stability, being highly labile at 37°C (Levenstein et al, 2006;Furue et al, 2008), causing bFGF production efforts to suffer from batch-to-batch variations, and high costs of production (Ueki et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lotz et al (Lotz et al, 2013) showed that FGF-2 levels fell to below 50% of the initial concentration within 4 h, and <25% remained after 24 h, presumably due to denaturation of FGF-2 by heat (Chen et al, 2012), proteolytic enzymes and growth factor-solvent interactions. Consequently, encapsulation into a polyelectrolyte-modified 2-hydroxyethyl methacrylate hydrogel (Galderisi et al, 2013), poly(lactic- co -glycolic acid) (PLGA) microspheres (Lotz et al, 2013) and multi-trilayered nanofilms (Han et al, 2017) have been investigated to achieve controlled release of FGF-2 in stem cell culture media. Controlled release of growth factors, as a means of enhancing the proliferation of cells in the central nervous system, has also principally involved incorporation into polymeric hydrogels (Gupta et al, 2006; Kapur and Shoichet, 2004; Kang et al, 2009; Jimenez Hamann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…2 From the same starting materials, polyelectrolytes can form a number of different structures, including polyelectrolyte multilayer (PEM) coatings, polyelectrolyte complexes (PECs), complex coacervates, or microcapsules. [3][4][5][6][7][8][9][10][11][12] The structure and properties of the resulting material depend on factors including the assembly method, polyelectrolyte concentrations, pH, and temperature. 3,[13][14][15] For this reason, polyelectrolytes have been used for a range of cell scaffolds and surface coatings capable of releasing specific nanoparticles, pharmaceuticals, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…3,[13][14][15] For this reason, polyelectrolytes have been used for a range of cell scaffolds and surface coatings capable of releasing specific nanoparticles, pharmaceuticals, and proteins. [7][8][9][10][11]16 PEMs specifically have been used extensively to control the release of growth factors (GFs) such as basic fibroblast growth factor (FGF2), bone morphogenetic protein (BMP-2), and transforming growth factor beta 1 (TGF-β1). 3,6,17,18 FGF2 is especially important for the growth of both fibroblasts and mesenchymal stem cells and is linked to improved proliferation and decreased cell death rate, and can also prevent differentiation to undesirable phenotypes.…”
Section: Introductionmentioning
confidence: 99%